LITERATURE REVIEW: STUDENTS' SCIENCE LITERACY SKILLS IN SCIENCE LEARNING - Laras Dyaz Handayani; Miterianifa, Miterianifa; Siska, Novia (BIOCHEPHY: Journal of Science Education, 2025)
The purpose of this study is to provide evidence that the science literacy approach can help students solve problems in science learning. The type of research used is the literature review method. This method is done by searching through Google Scholar. The analysis of twenty-five relevant journals showed ten articles discussing students' science literacy skills in science learning by solving problems in student learning. The science literacy skills of students in the experimental class are better than the control class, namely the average value of the experimental class is 79.71, while the control class is 71.71 according to the article with code A 10. One of the science learning models that can be used to develop students' science literacy is inquiry-based learning “Inquiry-based life-cycle thinking project”.